2022
DOI: 10.1186/s13578-022-00766-x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes as a potential compounding factor in COVID-19-mediated male subfertility

Abstract: Recent work indicates that male fertility is compromised by SARS-CoV-2 infection. Direct effects derive from the presence of viral entry receptors (ACE2 and/or CD147) on the surface of testicular cells, such as spermatocytes, Sertoli cells, and Leydig cells. Indirect effects on testis and concentrations of male reproductive hormones derive from (1) virus-stimulated inflammation; (2) viral-induced diabetes, and (3) an interaction between diabetes and inflammation that exacerbates the deleterious effect of each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 129 publications
(147 reference statements)
0
5
0
Order By: Relevance
“…Additionally persistent fever during viral infection might contribute to oxidative stress by reducing the levels of heat shock proteins (HSP). This could exacerbate the impact of ROS on spermatogenesis 26,43 . In a prolonged state of inflammation, there is a rise in the production of inflammatory signalling molecules like interleukins (IL‐1, IL‐6, IL‐8, IL‐10, IL‐17), TNF‐α and NF‐kβ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally persistent fever during viral infection might contribute to oxidative stress by reducing the levels of heat shock proteins (HSP). This could exacerbate the impact of ROS on spermatogenesis 26,43 . In a prolonged state of inflammation, there is a rise in the production of inflammatory signalling molecules like interleukins (IL‐1, IL‐6, IL‐8, IL‐10, IL‐17), TNF‐α and NF‐kβ.…”
Section: Discussionmentioning
confidence: 99%
“…This could exacerbate the impact of ROS on spermatogenesis. 26,43 In a prolonged state of inflammation, there is a rise in the production of inflammatory signalling molecules like interleukins (IL-1, IL-6, IL-8, IL-10, IL-17), TNF-α and NF-kβ. This results in an escalation of reactive oxygen species (ROS) production, accompanied by an increase in polymorphonuclear leukocytes and granulocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Under the condition of diabetes, hyperglycemia is involved in the production of systemic inflammation. Chronic inflammation can cause testicular endocrine disorder and lead to male reproductive dysfunction by releasing inflammatory cytokines or directly and independently affecting the HPG axis and/or testicular cells (Jiang et al 2022 ). For example, IL-1β and CCL2 inhibit androgen synthesis by inhibiting the activity of steroid-producing enzymes and ultimately induce apoptosis in Leydig cells (Jiang et al 2020 ).…”
Section: Potential Mechanism Of Male Infertility Induced By Diabetesmentioning
confidence: 99%
“…The study found that the interaction between inflammation and diabetes further aggravates the impact of both on the male reproductive system. The related mechanisms mainly include excessive accumulation of ROS, excessive release of cortisol, decreased level of triiodothyronine, and misalignment of activin/statin/follistatin axis (Jiang et al 2022 ). In addition, hyperglycemia induces inflammation of the male reproductive system, leading to sperm damage and male infertility, and may also be associated with the repolarization of tissue macrophages from the anti-inflammatory M2-like subtype to the pro-inflammatory M1-like subtype (Tavares et al 2017 ).…”
Section: Potential Mechanism Of Male Infertility Induced By Diabetesmentioning
confidence: 99%
“…Among men who had confirmed COVID-19 infection, a higher proportion of individuals had pre-existing conditions such as diabetes mellitus, hyperlipidemia, hypertension, and hypogonadism ( 30 ). Additionally, diabetes and obesity are associated with lowered testosterone levels, testicular dysfunction, and inflammation, which can compromise the MRT ( 31 ). Studies have found diabetic patients with severe COVID-19 are more susceptible in developing orchiepididymitis; of these cases, testicular pain leading to necrosis in the seminiferous tubule and significant calcification in the testicular artery was found during diagnosis ( 32 ), which may suggest that COVID-19 could trigger systemic vasculitis ( 33 ).…”
Section: Introductionmentioning
confidence: 99%